(untitled) (Development Engineering Conferences Center Articles Database, 2025)
While regular exercise training is known to decrease oxidative stress (OS) and enhance antioxidant functions in adults, limited data exist on OS responses in the pediatric population. This study aimed to investigate the effects of high-intensity functional training (HIFT) on oxidative stress and physical performance in adolescent soccer players. In this randomized controlled trial, 20 well-trained adolescent soccer players were divided into HIFT (n=10) and moderate-intensity soccer technical training (MITT, n=10) groups. Both groups trained for 8 weeks (3 days/week). Oxidative stress biomarkers (MDA, 8-OHDG, H2O2, GPx, CAT) and physical performance (VO2peak, vertical jump height [VJH], maximal explosive power [MEP]) were assessed pre- and post-intervention. Repeated measure mixed ANOVA (2×2) with a significance level of P<0.05 was used to determine differences between and within subjects. The main effect of interaction was significant for VO2peak, VJH and MEP (P<0.05). The main effect of interaction was not significant for CAT, 8-OHDG, GPx, H2O2 and MDA (P>0.05). Following intervention, VO2peak and VJH performance in the HIFT were significantly higher than MITT (P<0.05). MDA and H2O2 in the HIFT decreased significantly (P<0.05), but no significant changes were observed in the MITT (P>0.05). CAT activity decreased significantly (P<0.05), while GPx activity increased significantly (P<0.05) in both groups. 8-OHDG did not show significant changes in both groups (P>0.05). Eight weeks of HIFT did not cause greater OS compared to MITT, while could improve physical performance parameters. These findings suggest that HIFT is a viable and time-efficient training strategy for enhancing athletic performance in youth sports.